1998
DOI: 10.1006/viro.1998.9091
|View full text |Cite
|
Sign up to set email alerts
|

DNA Packaging by L1 and L2 Capsid Proteins of Bovine Papillomavirus Type 1

Abstract: Encapsidation of circular DNA by papillomavirus capsid protein was investigated in Cos-1 cells. Plasmids carrying both an SV40 origin of replication (ori) and an E. coli ori were introduced into Cos-1 cells by DNA transfection PV capsid proteins were supplied in trans by recombinant vaccinia viruses. Pseudovirions were purified from infected cells and their packaged DNA was extracted and used to transform E. coli as an indication of packaging efficacy. VLPs assembled from BPV-1 L1 alone packaged little plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 41 publications
3
47
0
1
Order By: Relevance
“…L2 has been shown to be necessary for DNA packaging in some PV types (16,57,58) and is likely to have additional roles during infection. As envisioned in the proposed model, L2 has the novel postentry role of delivering the genome to ND10, where it can be efficiently transcribed, in contrast to other nuclear DNA viruses, which initially localize to ND10 and then induce ND10 dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…L2 has been shown to be necessary for DNA packaging in some PV types (16,57,58) and is likely to have additional roles during infection. As envisioned in the proposed model, L2 has the novel postentry role of delivering the genome to ND10, where it can be efficiently transcribed, in contrast to other nuclear DNA viruses, which initially localize to ND10 and then induce ND10 dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they made use of heterologous systems in which L1 and L2 were overexpressed in irrelevant cell types from heterologous promoters in the context of viral or plasmid-based expression vectors, and the viral genome or some heterologous plasmid to be packaged was provided in trans via transfection, sometimes under conditions in which the DNA being packaged was highly amplified using a simian virus 40 replication origin. These nonphysiological conditions likely contribute to the fact that in some cases L2 is observed to influence the degree of DNA encapsidation (4,20,25,26,32,33) and in others it is not (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Different investigators have obtained conflicting results. Some found that in their system L2 was required for the encapsidation of viral or reporter DNA (4,20,25,26,32,33). In other systems L2 was not required (28,29).…”
mentioning
confidence: 99%
“…A consequence of the extensive regulation of the late phase of the papillomavirus life cycle is that recapitulating the assembly of papillomaviruses in cultured cells has posed a substantial challenge. A variety of systems have been developed for in vitro production of infectious papillomaviruses and papillomavirus-based gene transfer vectors (which are also known as papillomavirus pseudoviruses) (5,6,16,25,28,35,41,47,49). However, currently available systems are technically demanding and relatively low-yield.…”
mentioning
confidence: 99%